Linear social interactions models - Lawrence E. Blume; William A. Brock; Steven N. Durlauf; Rajshri Jayaraman (Institute for Advanced Studies (IHS), 2013)
This paper provides a systematic analysis of identification in linear social interactions models. This is both a theoretical and an econometric exercise as the analysis is linked to a rigorously delineated model of interdependent decisions. We develop an incomplete information game that describes individual choices in the presence of social interactions. The equilibrium strategy profiles are linear. Standard models in the empirical social interactions literature are shown to be exact or approximate special cases of our general framework, which in turn provides a basis for understanding the microeconomic foundations of those models. We consider identification of both endogenous (peer) and contextual social effects under alternative assumptions on a priori information about network structure available to an analyst, and contrast the informational content of individual-level and aggregated data. Finally, we discuss potential ramifications for identification of endogenous group selection and differences between the information sets of analysts and agents.
Keywords: C21; C23; C31; C35; C72; Z13; 330; Social interactions; identification; incomplete information games; Soziale Beziehungen; Soziales Verhalten; Unvollkommene Information; Nichtkooperatives Spiel; Theorie